2021
DOI: 10.3390/mi12030319
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication Methods for Microfluidic Devices: An Overview

Abstract: Microfluidic devices offer the potential to automate a wide variety of chemical and biological operations that are applicable for diagnostic and therapeutic operations with higher efficiency as well as higher repeatability and reproducibility. Polymer based microfluidic devices offer particular advantages including those of cost and biocompatibility. Here, we describe direct and replication approaches for manufacturing of polymer microfluidic devices. Replications approaches require fabrication of mould or mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
158
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(201 citation statements)
references
References 232 publications
1
158
0
Order By: Relevance
“…The latest photocuring 3DP technique, LCD printing, offers advantages such as affordable printers and good resolution [ 36 ]. Vat polymerisation allows for impressively small flow channel cross sections, but nevertheless wider channel dimensions were used in this work since it is often difficult to remove resin from the channels when their width is limited [ 37 ]. In addition, this study demonstrated that the developed microfluidic devices allow for the production of liposomes comparable in size to those produced using a commercial device.…”
Section: Discussionmentioning
confidence: 99%
“…The latest photocuring 3DP technique, LCD printing, offers advantages such as affordable printers and good resolution [ 36 ]. Vat polymerisation allows for impressively small flow channel cross sections, but nevertheless wider channel dimensions were used in this work since it is often difficult to remove resin from the channels when their width is limited [ 37 ]. In addition, this study demonstrated that the developed microfluidic devices allow for the production of liposomes comparable in size to those produced using a commercial device.…”
Section: Discussionmentioning
confidence: 99%
“…Terminals with desktop CNC micro-milling machines may, for instance, cost several thousand USD for basic versions or up to USD 100 k for high-end devices [ 10 , 11 , 41 ]. The prices of laser engraving stations depend on the power and quality of the laser optics and sophisticated desktop versions of heavy-duty CO 2 lasers for microchannel fabrication cost a few thousand USD or more, depending on the device specification [ 43 ]. Obviously, more highly priced systems will have the advantage of advanced technical specifications, and they may, for instance, incorporate a compact system enclosure, machine cabinet air filtering and cabinet and drilling stage temperature control, automatic tool change (ATC), auto-bed leveling and calibration, multiple nozzle printing, multiple axis milling, and hard- and software adaptations, permitting more complex 3D printing and micro-milling operations and the reduction of overall fabrication time.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the drive to improve treatment options to address these disadvantages has intensified in recent years. Other research [ 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ] looked at the effect of the defects on the mechanical efficiency of FRC and subsequently discussed treatment options for removing or minimizing them to improve the functional properties of the fabricated parts. Since FRCs are made up of a polymeric matrix and a short or continuous fiber reinforcement, the analysis will go through the effects of AM parameters such as infill pattern, layer thickness, raster angle, and fiber orientation on both thermoplastic polymers and FRCs printed using FDM technology.…”
Section: Some Important Am Flowcharts and Algorithmsmentioning
confidence: 99%